THE POLICY OF RAISING A HEALTHY GENERATION AND PROTECTING HEALTH IN THE REPUBLIC OF UZBEKISTAN - Beknazarovich, Ernazarov Abduvali (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The main objective is to raise a healthy and well-rounded generation, promote a healthy lifestyle culture, and protect the health of citizens. Method: The government has developed various documents, decrees, and decisions aimed at protecting health. Results: In safeguarding the health of every citizen, human rights are ensured and guaranteed by the state. Novelty: Human rights are ensured and guaranteed by the state in the context of public health protection.